'Bioethical Realism': A Framework for Implementing Universal Research Ethics. Issue 3 (6th August 2018) - Barugahare, John
Abstract: Implementation of existing ethical guidelines for international collaborative medical and health research is still largely controversial in sub‐Saharan Africa for two major reasons: One, they are seen as foreign and allegedly inconsistent with what has been described as an 'African worldview', hence, demand for their strict implementations reeks of 'bioethical imperialism'. Two, they have other discernible inadequacies – lack of sufficient detail, apparent as well as real ambiguities, vagueness and contradictions. Similar charges exist(ed) in other non‐Western societies. Consequently, these guidelines have been correctly judged as an inadequate response to the complex and ever shifting dilemmas met by researchers and research regulators in the field. This paper proposes a framework for effective implementation of existing guidelines without much worry about bioethical imperialism and other inadequacies. This framework is proposed using an analogy of Legal Realism, specifically its key assertions on how, in reality, judicial systems operate using general legal rules to settle specific cases. Legal realists assert that in judicial decision‐making, general legal rules do not totally dictate court decisions in specific cases. This analogy is used to coin a new term, 'Bioethical Realism.' The framework suggests that local Research Ethics Committees ought to be construed as analogues of judicial courts with the resulting implications. Consequently, just like legal rules are general rules that do not always dictate court decisions, similarly international bioethical guidelines are general ethical rules that should not always dictate local RECs' decisions and such decisions (ought to) enjoy considerable immunity from outsiders.